Checklist of invertebrates and conspicuous fishes in rocky reefs and Sargassum beds in the North Pacific of Costa Rica - Suárez, Alvin (2021)
Introduction: The marine biodiversity is well known in some areas and for some marine ecosystems of the Pacific coast of Costa Rica. The marine sector of Área de Conservación Guanacaste, in the North Pacific of the country, is a priority area for conservation of marine and coastal biodiversity.Objective: Our aim was to increase the knowledge of marine biodiversity in a conservation priority site in Costa Rica and in poorly or scarcely studied marine ecosystems, such as rocky reefs and Sargassum beds, respectively.Methods: The study was conducted in Bahía Salinas and Golfo de Santa Elena in 2013. In January, four rocky reefs were visited; while in February three rocky reefs and one Sargassum bed were visited. We identified the macroinvertebrates and conspicuous fish species through underwater visual census methods (timed swim and band transects). The mean density of each species was estimated through band transects method. Results: A total of 25 invertebrates and 34 fish species were identified. We found a high number of species of invertebrates (23) and fish species (33) in rocky reefs, but few species on Sargassum beds (eight invertebrates and ten fish species).Species composition differed between marine ecosystems. Conclusions: Our study further evidence the limited knowledge of invertebrates and fish communities in these marine ecosystems in the North Pacific of Costa Rica. Considerably more surveys and field work are required to support management decisions that are backed by sound scientific knowledge.